Emerging Applications of Control and Systems Theory A Festschrift in Honor of Mathukumalli Vidyasagar (Lecture Notes in Control and Information Sciences - Proceedings,, 2018)
This book celebrates Professor Mathukumalli Vidyasagar's outstanding achievements in systems, control, robotics, statistical learning, computational biology, and allied areas. The contributions in the book summarize the content of invited lectures given at the workshop "Emerging Applications of Control and Systems Theory" (EACST17) held at the University of Texas at Dallas in late September 2017 in honor of Professor Vidyasagar's seventieth birthday. These contributions are the work of twenty-eight distinguished speakers from eight countries and are related to Professor Vidyasagar's areas of research. This Festschrift volume will remain as a permanent scientific record of this event.